From Hospital to Home Care: Creating a Domotic Environment for Elderly and Disabled People - López Celani, Natalia Martina (2016)
Advances in medicine have led to a significant increase in human life expectancy and, therefore, to a growing number of disabled elderly people who need chronic care and assistance [1]. The World Health Organization reports that the world's population over 60 years old will double between 2000 and 2050 and quadruple for seniors older than 80 years, reaching 400 million [2]. In addition, strokes, traffic-related and other accidents, and seemingly endless wars and acts of terrorism contribute to an increasing number of disabled younger people.